Descubrimiento de pruebas en la ley 906 de 2004 (2016)
In testing we found the discovery of a thorough analysis from the initial moment when there is knowledge of the commission of an offense, it should be clearly affecting a fundamental right or a legally well protected. The Attorney General's Office is responsible for collecting and packing everything in the commission of the act is considered as an element evidentiary material and lead to clarify the facts, all the practices carried out by researchers from this body should be verified by the prosecutor in charge of bringing charges to reach the certainty of what will present to the trial judge and then take the decision to make complaint, file charges, request preclusion or even reach the principle of opportunity. Arrived at the time of the preliminary hearing the prosecutor must make mention of the material evidence that used during the trial to clarify the facts to be subsequently discovery of evidence and given the opportunity to defend contest them, both parties undertake this discovery outside audience and before starting the trial